PENGARUH LEVERAGE, FIRM SIZE, DAN LIQUIDITY TERHADAP PROFITABILITY - Effendi, Pricyllia; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the effect of leverage (DER), firm size (SIZE), and liquidity (CR) on profitability (ROA) of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019. The sample was selected using purposive sampling technique and the valid data were 73 companies. The data processing technique using multiple regression analysis was carried out using the random effects method assisted by the E-views 12 program and Microsoft Excel 2010. The results of the partial study showed that there was a significant negative effect between leverage on profitability, company size had a significant positive effect on profitability. And liquidity had no effect on profitability.